2019
DOI: 10.2147/ccide.s221742
|View full text |Cite
|
Sign up to set email alerts
|

<p>Mechanical properties of experimental resin cements containing different photoinitiators and co-initiators</p>

Abstract: AimThe aim of this study was to evaluate the influence of different concentrations of two photoinitiators and one co-initiator on the flexural strength (FS) and elastic modulus (E) of experimental resin cements.Materials and methodsA mixture containing BisGMA, TEGDMA, and barium-aluminum-silicate (BaAlSi) and silanized colloidal silica (SiO2) filler particles was prepared with two photoinitiators, viz. camphorquinone (CQ) and bisacylphosphine oxide (BAPO). Dimethylaminoethyl methacrylate (DMAEMA) was used as c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
1
3
0
1
Order By: Relevance
“…A better performance of the BAPO group was also observed through the mechanical properties analysis, showing results consistent to those found in similar studies 16,28 . The results can be justified by their polymerization reaction independent of the presence of a co-initiator (amine), allowing a fast photolysis of its molecule for free radical generation and greater molar extinction coefficient in relation to PPD and CQ.…”
Section: Discussionsupporting
confidence: 90%
“…A better performance of the BAPO group was also observed through the mechanical properties analysis, showing results consistent to those found in similar studies 16,28 . The results can be justified by their polymerization reaction independent of the presence of a co-initiator (amine), allowing a fast photolysis of its molecule for free radical generation and greater molar extinction coefficient in relation to PPD and CQ.…”
Section: Discussionsupporting
confidence: 90%
“…De igual manera, entre las desventajas que presenta esta lámpara se encuentran el ruido que emite, su alto costo y su tamaño, que la hace poco práctica para transportar 19 . Las lámparas de tipo argón poseen una intensidad de 800 mw/cm 2 y un rango de onda de 476,5 a 480 nm, compatibles con los materiales que presentan como fotoiniciador a la canforoquinona 20 , pero son poco utilizadas porque emiten mucho calor y generan contracción de fotopolimerización elevada en los materiales 21 . A finales de los 90, aparecieron las primeras lámparas de diodo emisor de luz (lámparas led), que comenzaron a utilizarse en la odontología como lámparas de fotopolimerización.…”
Section: Resultsunclassified
“…[60] They shed light on the different induction periods or conversion rates obtained depending on the nature of the photoinitiator. [58,60,61] Moreover, not only the nature but also the concentration of the photoinitiator influences the printing parameters. Indeed, with a lower amount of photoinitiator, longer exposure times are needed to reach the same layer thickness.…”
Section: Photoinitiatormentioning
confidence: 99%
“…This shows a direct link between the photoinitiator content and mechanical properties. [61,63,64] Wang et al tried to optimize the concentration of the camphorquinone photoinitiator in their acrylate-based resin to achieve the best mechanical properties. [65] They observed that the degree of conversion (obtained by near-infrared spectroscopy), the mechanical properties (elastic modulus and hardness), as well as the curing depth D p (in Jacobs' law) were maximized for an optimum photoinitiator concentration.…”
Section: Photoinitiatormentioning
confidence: 99%
See 1 more Smart Citation